Simulation of dual fibre Bragg gratings as a fabry-perot tunable filter - Md. Rashid, Siti Nafisah (2010)
A Fabry-Perot Bragg Gratings (FP-BG) is developed by using two uniform fibre Bragg gratings (FBG) system. The objective of this research is to simulate single, dual FBGs and fabricate single FBG by using phase mask writing with a UV KrF excimer laser. Three single FBGs with Bragg wavelength of 1551.09 nm, 1551.29 nm and 1551.66 nm have been fabricated with reflectivity values of 30.2%, 78.1% and 44.7% respectively. FBG’s with reflectivity value of 78.1% are categorized as good and strong FBG, since its reflectivity value is more than 50%. Some simulation works were also executed in this research to generate the transmission spectrum of single and dual FBGs. For single FBG, the transmission spectra for different values of grating lengths and reflectivities have been studied. Results showed that the transmission spectra of single FBG becomes wider if the grating produced is short, and longer when the reflectivity value is increased. For dual FBGs, simulations were performed by varying the separation distance between the two FBGs. The separation distance was varied from 0.5 cm to 5.5 cm, with an increment of 0.5 cm. The result showed that any increase of the separation distance led to an increase in the number of maximum transmission peaks of dual FBGs, due to the absorption phenomenon. Only selected wavelengths with certain frequencies were allowed to transmit at the fibre’s end and the dual FBGs performed acted as a Fabry-Perot filter. This new configuration of FP filter exhibited similar behaviours as the conventional FP etalon, in which the parameters of free spectral range (FSR), full-width-half-maximum (FWHM) and finesse can be obtained from the transmission profiles.